What are the risks of manual treatment of the spine? A scoping review for clinicians - Gabrielle Swait; Rob Finch (Chiropractic & Manual Therapies, 2017)
Abstract Background Communicating to patients the risks of manual treatment to the spine is an important, but challenging element of informed consent. This scoping review aimed to characterise and summarise the available literature on risks and to describe implications for clinical practice and research. Method A methodological framework for scoping reviews was followed. Systematic searches were conducted during June 2017. The quantity, nature and sources of literature were described. Findings of included studies were narratively summarised, highlighting key clinical points. Results Two hundred and fifty articles were included. Cases of serious adverse events were reported. Observational studies, randomised studies and systematic reviews were also identified, reporting both benign and serious adverse events. Benign adverse events were reported to occur commonly in adults and children. Predictive factors for risk are unclear, but for neck pain patients might include higher levels of neck disability or cervical manipulation. In neck pain patients benign adverse events may result in poorer short term, but not long term outcomes. Serious adverse event incidence estimates ranged from 1 per 2 million manipulations to 13 per 10,000 patients. Cases are reported in adults and children, including spinal or neurological problems as well as cervical arterial strokes. Case-control studies indicate some association, in the under 45 years age group, between manual interventions and cervical arterial stroke, however it is unclear whether this is causal. Elderly patients have no greater risk of traumatic injury compared with visiting a medical practitioner for neuro-musculoskeletal problems, however some underlying conditions may increase risk. Conclusion Existing literature indicates that benign adverse events following manual treatments to the spine are common, while serious adverse events are rare. The incidence and causal relationships with serious adverse events are challenging to establish, with gaps in the literature and inherent methodological limitations of studies. Clinicians should ensure that patients are informed of risks during the consent process. Since serious adverse events could result from pre-existing pathologies, assessment for signs or symptoms of these is important. Clinicians may also contribute to furthering understanding by utilising patient safety incident reporting and learning systems where adverse events have occurred.